Project and Realization of a Wide-Range High-Frequency RFID Gate Allowing Omnidirectional Detection of Transponders. (8th February 2012) - Benelli, Giuliano; Parrino, Stefano; Pozzebon, Alessandro
Abstract : We describe the study and development of a 2-meter-wide HF RFID gate providing omnidirectional detection of transponders. Common commercial HF RFID gate structures provide a maximum reading range around 150 cm. Moreover, this value is in most cases guaranteed only for the maximum coupling direction, with lower values for the other 2 orientations. The proposed structure raises the value of the reading range up to 200 cm for every orientation of the transponder, with even better results (220 cm) when the transponder is in the position of maximum coupling. This result has been achieved through numerical simulations, focused on the study of the geometry of the antenna system and on the realization of the matching circuit and then confirmed with the physical implementation of the system.